Pemanfaatan Lahan Pekarangan untuk Budidaya Sayuran dan Pembuatan Pupuk Organik Cair di Kelurahan Gambesi - Nurhikmah; Irmayanti, Laswi; Wulandari, Angela; Dewi, Eka Kusuma; Fatrawana, Adesna (Jurnal Pengabdian Masyarakat Hutan, 2023)
Planting plants does not necessarily require a large area of ​​land, but can be done at home by utilizing existing yard space. Food is a primary life need that must be met. The utilizing of home garden as agricultural land can help fulfill the family's daily food needs. Apart from that, household organic waste can also be processed into organic fertilizer to support the growth of plants planted in the yard. People in Gambesi generally cultivate water spinach to meet their daily food needs and also to sell. The community wants the addition of other types of plants that are easy to develop. Apart from that, people need knowledge about making organic fertilizer to help fertilize the plants in their yards. Therefore, this community service is carried out with the aim of educating and socializing how to make liquid organic fertilizer from household waste and planting vegetables in home gardens to meet the community's daily food needs. Keywords: vegetable cultivation, home garden, organic fertilize